The Role of Extracurricular Activities in Internalizing Hindu Religious Values at SD Negeri 3 Amparita - Ketut Erawati; I Made Luwih (Jayapangus Press, 2023)
This study aims to determine the role of extracurricular activities in internalizing Hindu religious values at UPT SDN 3 Amparita. The method used is qualitative with a descriptive research approach. Data collection was carried out using interviews, observation, and documentation. The research subjects consisted of teachers and students at UPT SDN 3 Amparita. The results showed that extracurricular activities play an important role in internalizing Hindu religious values. Extracurricular activities carried out at UPT SDN 3 Amparita are in the form of spiritual activities, joint viewing activities, introduction to Hinduism, and moral lessons. These activities increase students' awareness of Hindu values and assist them in integrating them into their lives. The results of this study indicate that extracurricular activities are one of the effective efforts in strengthening the internalization of Hindu religious values at UPT SDN 3 Amparita.